AUTOMATION OF THE PROCESS OF MAKING INVENTORY OF BASIC TOOLS AND FINISHED PRODUCTS (Modern education and development, 2025)
In this article, the analytical results on the inconvenience of counting finished products and fixed assets in warehouses are carried out.